Efficiency Analysis of Sharia Ventura Capital Companies Using Data Envelopment Analysis (DEA) Period 2014 – 2018 - Fitri Sulistyorini; Rosida Dwi Ayuningtyas (Department of Islamic Economic, Faculty of Economic and Business, Nahdlatul Ulama Islamic University (UNISNU) Jepara, Indonesia, 2022)
Efficiency is one of the performance parameters that theoretically underlies the entire performance of a venture capital company. A lot of research on the efficiency of venture capital companies mostly focuses on conventional venture capital companies. Recently, Islamic venture capital companies have developed in various regions in Indonesia and are operated in a modern and sharia manner like other Islamic venture capital companies. This study evaluates the efficiency performance of Islamic venture capital companies in the period 2014 - 2018 (this study uses annual data) using Data Envelopment Analysis (DEA), where the first step is to measure the technical efficiency performance of venture capital companies using Data Envelopment Analysis (DEA) with using an intermediation approach. Based on the efficiency measurement using the DEA method, it shows that the Sharia Venture Capital Company during the 2014 - 2018 period was still inefficient. The efficiency value of the most efficient venture capital company is 100%. The data used in this study is secondary data, collected from financial reports published by the Financial Services Authority (OJK) and the websites of each company. The sampling technique used in this study was purposive sampling by taking a sample of 5 (five) Islamic venture capital companies. The input variables used in this study are total assets, capital and labor costs. While the output variable includes financing and revenue sharing.